Characterization and antioxidant activity of bitter vetch protein-based films containing pomegranate juice. (December 2016) - Arabestani, Akram; Kadivar, Mahdi; Shahedi, Mohmmad; Goli, Sayed Amir Hossein; Porta, Raffaele
Abstract: The effect of different amounts of pomegranate ( Punica granatum, Malas Isfahan cultivar) juice, endowed with high antioxidant activity, on the bitter vetch seed protein films was investigated. We demonstrated that the films prepared in the presence of pomegranate juice exhibited significantly increased moisture content, total soluble matter, elongation at break, as well as water vapour permeability, whereas their tensile strength significantly decreased. These findings clearly suggest that pomegranate juice had a plasticizing effect on the prepared protein-based films, the antioxidant activity of which was also found significantly enhanced. Since scanning electron microscopic images indicated that film structure was undoubtedly affected, we hypothesized that interactions between phenolic compounds contained in the pomegranate juice and bitter vetch proteins are responsible for the modified properties of the obtained blended films. The potential use of pomegranate juice in improving the antioxidant activity of protein-based films is suggested. Highlights: Bitter vetch protein-based films containing pomegranate juice were prepared. Pomegranate juice had a marked plasticizing effect on the films. Pomegranate juice significantly enhances film antioxidant activity. The use of pomegranate juice containing films in food packaging was suggested.